Keller-Osserman Estimates for Some Quasilinear Elliptic Systems - Yarur-Said, C (2013)
In this article we study quasilinear systems of two types, in a domain ? of ?N : with absorption terms, or mixed terms: Equation Presented where ?, ? > 0 and 1 < p; q < N; and D = ?? - (p - 1)(q - 1) > 0; the model case is Ap = ?p; Aq = ?q: Despite of the lack of comparison principle, we prove a priori estimates of Keller-Osserman type: Equation Presented Concerning system (M); we show that v always satisfies Harnack inequality. In the case ? = B(0; 1){0}, we also study the behaviour near 0 of the solutions of more general weighted systems, giving a priori estimates and removability results. Finally we prove the sharpness of the results.